Musical Pilgrimages to Cuba: Negotiating Tourism and Musical Learning in Cuban Batá Drumming - Windress, Kent (MUSICultures, 2016)
This paper seeks to examine aspects of intercultural music learning and teaching using the case studies of foreigners travelling to Cuba who learn and perform ceremonial batá drumming. Through ethnography and an analysis of the Cuban tourist industry, I situate the particular experiences of my participants in the broader context of the Cuban tourist industry. I focus on the experiences of my participants as they develop networks of musical learning and become involved in ceremonial batá performance, highlighting how they have the potential to create lasting relationships that are of benefit to all parties involved.